Is it Worth the Money? The Functionality of Engineered Shallow Stream Banks as Habitat for Juvenile Fishes in Heavily Modified Water Bodies. (22nd July 2016) - Pander, J.; Mueller, M.; Knott, J.; Egg, L.; Geist, J.
Abstract: Heavily modified water bodies (HMWB) are characterized by monotonous and straightened channel morphologies with high degrees of bank enforcement. They often lack shallow bank habitats, which are considered important for critical life stages of fishes. In this study, three principle options to engineer shallow stream zones were assessed concerning the value of the created habitats for larval, juvenile and adult stages of fishes in 30 sites from three HMWB. The construction scheme of the juvenile habitats comprised different degrees of embankment ranging from rip‐rap structures with steep bank angles to almost nature‐like construction schemes with very flat river‐banks and sparing usage of structural enrichment such as boulders and dead wood. In general, the differences between the three habitat types were more pronounced in density of different life stages than in the presence or absence of species or certain life stages. A steep bank angle and a high degree of engineering such as placement of rip‐rap embankment, boulders or dead wood structure in the habitats were hardly accepted by early larval and juvenile stages of rheophilic fishes. In contrast, the construction scheme of a nature‐like habitat with a flat bank angle (<10%), low water depth (mean = 24 cm) and a sparing usage of coarse woody debris (CWD) and boulders had the highest success. Other investigated habitat types did not provide additional benefit, neither in terms of supporting additional species and life stages, nor in high individual numbers and should thus only be implemented when land for restoration is scarce and nature‐like habitats cannot be realized. Copyright © 2016 John Wiley & Sons, Ltd.